Modulation by Polymyxin-B Hemoperfusion of Inflammatory Response Related to Severe Peritonitis. Issue 1 (January 2017) - Coudroy, Rémi; Payen, Didier; Launey, Yoann; Lukaszewicz, Anne-Claire; Kaaki, Mahmoud; Veber, Benoit; Collange, Olivier; Dewitte, Antoine; Martin-Lefevre, Laurent; Jabaudon, Matthieu; Kerforne, Thomas; Ferrandière, Martine; et al.
Abstract : ABSTRACT: Conflicting results have been reported on the influence of Polymyxin-B hemoperfusion treatment on systemic inflammation markers. The aim of the study was to assess in a randomized control trial the influence on plasma cytokine concentrations of Polymyxin-B hemoperfusion in septic shock due to peritonitis. A panel of 10 pro- or anti-inflammatory cytokines was measured in 213 patients with peritonitis-induced septic shock enrolled in the randomized trial ABDOMIX testing the impact of 2 Polymyxin-B hemoperfusion sessions with standard treatment. Gram-negative bacteria were identified in 69% of patients. In the overall population, baseline plasma cytokine concentrations were not different between the two groups. Circulating tumor necrosis factor-α, interleukin (IL)-1β, IL-10, IL-6, and IL-1RA decreased significantly over time in both groups ( P <0.0001 for all in controls, and P = 0.0002, 0.003, and <0.0001 in patients treated with Polymyxin-B hemoperfusion). IL-17A decreased significantly in patients treated with Polymyxin B hemoperfusion ( P = 0.045) but not in controls. At the end of the second Polymyxin-B hemoperfusion session or at corresponding time in controls, plasma levels of cytokines did not differ between the two groups. Similar results were found in the subgroup of patients with gram-negative peritonitis who completed two Polymyxin-B hemoperfusion sessions. These results do not support a significant influence of Polymyxin-B hemoperfusion on circulating cytokines assessed except for IL-17A which clinical significance remains to be elucidated.